Teaching and learning in Project Management: what are the challenges? - Carreiro, Eduardo de Lima Pinto; Maccari, Emerson Antonio; Scafuto, Isabel Cristina (Revista de Administração da UFSM, 2023)
Purpose: The objective of this work is to understand how teaching and learning in project management happens and what their challenges are. Design/methodology/approach: To achieve this objective, we developed a Systematic Literature Review about teaching and learning in project management. Initially, we found 667 works. After reading the title, we selected 150 works for a full reading. 120 were suitable for the proposed objective. Findings: We found five categories: (1) learning; (2) teaching; (3) education; (4) skills; and (5) knowledge. Originality/value: We observed that there are gaps in the studies dealing with these themes concerning project management. Topics such as management of learning processes, the relationship between learning in educational institutions and organizational environments, the impact of informal learning, experiential learning, comparison of serious games and simulations with other learning methods, serous games in projects, hard skills, and soft skills, are still not widely published in academic journals on project management.